Monitoring oxidation during the storage of pressure-treated cooked ham and impact on technological attributes. Issue 8 (August 2019) - Rakotondramavo, Anja; Ribourg, Lucie; Meynier, Anne; Guyon, Claire; de Lamballerie, Marie; Pottier, Laurence
Abstract: High-pressure processing is a post-processing preservation method commonly used on meat products. However, it can affect the structural properties and the physico-chemical properties of the meat. The aim of this study was to compare the physical properties, lipid and protein oxidation of control and treated (500 MPa, 20 °C, 5 min) cooked ham during subsequent storage (21 days at 4 °C). High pressure processing induced increase of hardness and syneresis after 7 days of storage. The redness (a*) was slightly affected by the high pressure treatment but not the lightness (L*) and the yellowness (b*). However, the fluctuation of color was not clearly visible. Evaluation of primary (conjugated dienes) and secondary (malondialdehyde MDA and thiobarbituric reactive substances TBA-RS) lipid oxidation products showed that pressure increases oxidation of lipids. Whereas, high pressure processing had no immediate effect on MDA and TBA-RS content, higher amount compared to control were observed during the refrigerated storage. This lipid oxidation could be due to the release of prooxidant iron from hemoproteins after the high pressure treatment. Finally, the determination of free and accessible thiols showed that the high pressure treatment leads to a protein oxidation.